Case report: A novel de novo variant of NACC1 caused epileptic encephalopathy and intellectual disability - Wu, Jiahao; Gan, Jing; Hua, Yimin; Li, Yifei; Qie, Di (Frontiers in Psychiatry, 2024)
Background Genetic disorders could also contribute to intellectual disability. Using whole exome sequencing (WES), several variants have been identified as autosomal-dominant inheritance intellectual disability. Thus, the application of WES has demonstrated its critical role in distinguishing intellectual disability in children patients, which provides essential diagnosis and promotes therapeutic strategy. Case presentation The proband, an 18-month-old female patient, presented with a complex clinical profile characterized by profound developmental delay, epilepsy, and neurological developmental impairment. WES identified a heterozygous c.913A>G variant in exon 2 of NACC1, resulting in disease caused by a change in the amino acid sequence, affecting the protein features and resulting in splice site changes, as revealed by MutationTaster analysis. The protein structure of NAC1 was built and named AF-Q96RE7-F1, and the mutant site was beyond the BTB/POZ, NLS, and BEN domains. Subsequently, PyMOL software was used to illustrate the molecular structure between the wild type and the mutant type of NAC1. The residues around the 304 site of amino acid changed in NAC1 p.T304A with an altered hydrogen bond, indicating an unstable structure. The patient was diagnosed with intellectual disability and profound developmental delay with epilepsy harboring a novel de novo NACC1 variant. Upon hospital admission, a comprehensive treatment regimen was initiated, including antiseizure medications, nutritional supplements, and rehabilitation training. As a result, the patient’s movement performance improved. However, recurrent epilepsy attacks still occurred. Conclusion This is the first case revealing a novel NACC1 c.903A>G variant that induced a neurological impairment in an infant. This report expanded the understanding of the non-domain-associated variant of NACC1 and developmental disorder.